Opportunities and Threats for Small Seaports in Poland in the Era of External Disturbances - Kaczerska, Dominika (Journal of Public Governance, 2024)
Objective: The aim of the article is not only to identify opportunities, threats, strengths, and weaknesses for selected small seaports in Poland, but, above, all to critically evaluate the extent to which the strategic documents and audits correspond with the actual situation in the ports. The article also formulates recommendations for improving strategic management in these entities. Research Design & Methods: The study is based on desk research, document analysis, literature review (Polish and international sources) as well as case studies of selected ports (Ustka, Darłowo, Kołobrzeg, Elbląg). The author’s contribution is the comparative assessment of the consistency between the SWOT analyses included in national strategic documents, Supreme Audit Office reports, and local port strategies. Findings: The comparison shows significant overlaps but also gaps between strategic plans and their implementation. Weaknesses such as insufficient infrastructure and fragmented ownership structure are repeated in all documents, but implementation lags undermine the ability to exploit opportunities, particularly in the offshore sector. The analysis identifies where national and local strategies diverge and why. Implications / Recommendations: Small seaports require better coordination between local authorities, port managers, and the ministry responsible for maritime economy. Recommendations include strengthening financial mechanisms, defining clearer roles of ports in the national economy, and improving integration with EU strategies. Contribution / Value Added: The article contributes by transforming descriptive SWOT data into a critical comparative analysis and strategic recommendations. It also expands the discussion by relating the Polish case to international literature on port governance and resilience under external shocks. Article classification: research article JEL classification: R42, R59